Bosnia and Herzegovina - The Road to Europe : Annex 5. Inland Waterways Transport - Realizing the Potential - World Bank (Washington, DC, 2013)
This report highlights deficiencies and indicates priorities for a prospective national transport strategy and action plan for further consideration by key stakeholders. The overall objective should be the development of a transport system, and an institutional framework, that facilitates rather than constrains, economic development in Bosnia and Herzegovina. A strong transport system contributes to economic growth by reducing the economic distance to markets by expanding opportunities for trade, by improving the competitiveness of national locations for production and distribution, and by facilitating mobility for a country s citizens; while minimizing the social and environmental costs of the transport sector. The report concludes by recommending actions that aim to improve the institutional framework, improve the sustainability of the transport sector, facilitate broad based economic growth, and mitigate the social and environmental detriments associated with transport. Specific policy recommendations are presented to accomplish these conclusions.